Method for preparing perovskite FAPbCl3 nanocrystal based on solution method

By using a combination of hydrochloric acid and organic solvents in the preparation of perovskite nanocrystalline materials, the problem of unstable preparation of organic solvent toxicity and thermal injection methods in the solution method is solved, and the preparation of high-performance FAPbCl3 perovskite nanocrystallines is realized. Suitable for mass production and demonstrates good optical performance.

CN119219523APending Publication Date: 2024-12-31CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411337588.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the existing preparation methods of perovskite nanocrystalline materials, the solution method uses organic solvents and is unfriendly in the environment, and the thermal injection method is difficult to control the preparation process, resulting in uneven grain sizes of nanocrystalline grains, rough surfaces, reduced light absorption performance and stable Poor sex.

Method used

Using hydrochloric acid, nitrogen-dimethylformamide and dimethylsulfoxide as reaction solvents, lead acetate and formidine acetate were added step by solution method, thoroughly stirring and suction filtration, and then dried in a tube furnace to reduce the organic solvent. Use and improve preparation controllability.

Benefits of technology

The prepared FAPbCl3 perovskite nanocrystals show good optical properties, uniform grain size, smooth surface, strong light absorption and high stability, and are suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219523A_ABST
    Figure CN119219523A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing perovskite FAPbCl3 nanocrystals, which comprises the following steps: by taking hydrochloric acid, nitrogen, nitrogen-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) as solvents, weighing, stirring, carrying out suction filtration, drying and the like to prepare perovskite FAPbCl3 crystal powder. The method comprises the following steps: 1) weighing a certain amount of hydrochloric acid, nitrogen, nitrogen-dimethyl formamide and dimethyl sulfoxide solution; (2) slowly pouring lead acetate and formamidine acetate solids into the solution in the step (1) in sequence; 3) fully stirring the solution, filtering, and cleaning with ethyl acetate to obtain perovskite nanocrystals; and 4) putting the product obtained in the step 3) into a tubular furnace, and drying in a dark place under a vacuum condition. The perovskite FAPbCl3 nanocrystal prepared by the invention is uniform in particle size, relatively good in fluorescence intensity, good in ultraviolet light absorption capacity and relatively wide in spectral response range, and a film prepared from the perovskite FAPbCl3 nanocrystal has relatively good carrier transport performance. The method can also be used for preparing various two-dimensional and three-dimensional perovskite nanocrystalline materials by a one-step method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Halogen perovskite nanocrystalline materials have shown significant advantages in experimental studies, including extremely high light absorption efficiency, high fluorescence quantum efficiency, and strong defect tolerance. In terms of electrical properties, these nanocrystalline materials exhibit excellent carrier transport properties, which make them shine in applications such as perovskite solar cells and photodetectors, helping to improve the performance of thin film materials and optimize energy level arrangement. Therefore, halogen perovskite nanocrystalline materials show great commercial application potential in the fields of optics and electricity. Due to their excellent optical and electrical properties, halogen perovskite nanocrystalline materials have shown broad application prospects in technical fields such as solar cells and photodetectors, and are expected to promote the development of related industries.

[0002] The present invention provides a method for preparing perovskite FAPbCl3 nanocrystals. The method comprises: using hydrochloric acid as Cl - source, hydrochloric acid, nitrogen, nitrogen-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) as the reaction solvent, and then lead acetate and formamidine acetate were added successively as Pb 2+ and FA + The source is added to the solvent, stirred thoroughly to obtain a nanocrystalline solution, filtered and washed with ethyl acetate, and dried to obtain perovskite FAPbCl3 nanocrystalline powder. The entire preparation process is carried out at room temperature.

[0003] At present, the mainstream methods for preparing perovskite nanocrystals include solution method, hot injection method and gas-assisted solution method. Among them, the solution phase method is the most commonly used method and the easiest method for large-scale production. The solution phase method is low-cost and easy to operate. However, the solubility problem of the solution is prominent. Since the solubility of various halides in solvents varies significantly, we must fully consider the ratio and combination of various solvents and solutes when configuring the solution. The organic solvents generally used in the solution phase method are toxic and unfriendly to the environment. Other perovskite nanocrystal powders prepared by hot injection methods are also difficult to control their preparation process, resulting in more powder phase defects and easy to be affected by the environment, which leads to problems such as uneven nanocrystal grain size, rough surface, decreased light absorption performance, and poor stability.

[0004] Therefore, developing a method to reduce the use of organic solvents and produce FAPbCl3 perovskite nanocrystals with good performance is an urgent problem to be solved. Summary of the invention

[0005] In order to prepare perovskite nanocrystals with better performance, the present invention provides a method for preparing FAPbCl3 perovskite nanocrystal materials.

[0006] The technical solution adopted by the present invention is as follows:

[0007] Step 1: Use deionized water, isopropanol and anhydrous ethanol to ultrasonically clean the filtration device, sample bottle and magnet used in the experiment, each for 10-15 minutes, and repeat 2-3 times. After the ultrasonic cleaning, put them in a drying oven for drying. After drying, use sealing film to seal the filtration device and sample bottle to prepare for the next step.

[0008] Step 2: weigh appropriate amounts of formamidine acetate (CH3COOFA), lead acetate (CH3COOPb), nitrogen, nitrogen-dimethylformamide and dimethyl sulfoxide in a glove box, weigh a certain amount of hydrochloric acid, hydrochloric acid, nitrogen, nitrogen-dimethylformamide, dimethyl sulfoxide, formamidine acetate and lead acetate at room temperature, and the weight percentages are: hydrochloric acid solution 0.1-20%, nitrogen, nitrogen-dimethylformamide 0.1-25%, dimethyl sulfoxide 0.1-30%, formamidine acetate 2-50% and lead acetate 1-45%. Pour lead acetate into the mixed solution of hydrochloric acid, nitrogen, nitrogen-dimethylformamide and dimethyl sulfoxide and stir thoroughly for 10-15 minutes, and keep the magnetic speed at 100-300rpm. After the lead acetate is completely dissolved, slowly add formamidine acetate, keep the pH value of the solution below 0-7 and slowly increase the speed to 500-800rpm. After the formamidine acetate is completely dissolved, the solution is stirred for 8-14 hours.

[0009] Step 3: Place a polytetrafluoroethylene filter membrane with a pore size of 0.1-0.4 microns in a suction filtration device and wet it with ethyl acetate. Pour the solution prepared in step 2 into the suction filtration device, place the filtered solid into a new sample bottle and pour in ethyl acetate, stir and wash for 10-20 minutes, repeat 5-7 times and store the obtained solid in the sample bottle. During the drying process, open the sample bottle cap and place the sample bottle in a tube furnace. The tube furnace is set to a temperature of 45-60°C, a heating rate of 3-8°C / min, and a heat preservation time of 20-48 hours. Finally, perovskite FAPbCl3 nanocrystals with good performance are obtained.

[0010] The present invention mainly adopts a solution method to prepare perovskite FAPbCl3 nanocrystals, using hydrochloric acid, DMF and DMSO as reaction solvents, and obtains perovskite FAPbCl3 nanocrystals through dissolution, stirring, suction filtration and tube furnace drying. The perovskite solution needs to be fully stirred for 8-14 hours, and the nanocrystal powder is dried in a tube furnace at 45-60°C for 20-48 hours. The product of the present invention, hydrochloric acid as Cl - source, hydrochloric acid, nitrogen, nitrogen-dimethylformamide and dimethyl sulfoxide as reaction solvents, and then lead acetate and formamidine acetate were added successively as Pb 2+ and FA +The source is added to hydrochloric acid, stirred thoroughly to obtain a nanocrystalline solution, then filtered and washed with ethyl acetate, and dried to obtain a perovskite FAPbCl3 nanocrystalline powder, which has good optical properties. This method has simple experimental steps and strong controllability, and is suitable for large-scale preparation of perovskite FAPbCl3 nanocrystals. The temperature of the tube furnace is set at 45-60℃, the heating rate is 3-8℃ / min, and the insulation time is 20-48 hours. Finally, take out the sample and seal it for storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is an XRD characterization result diagram of the FAPbCl3 perovskite nanocrystal prepared in the present invention.

[0012] Figure 2 This is a SEM characterization result diagram of the FAPbCl3 perovskite nanocrystal prepared in the present invention.

[0013] Figure 3 This is a statistical result diagram of the particle size of the FAPbCl3 perovskite nanocrystals prepared in the present invention.

[0014] Figure 4 This is a UV-vis absorption spectrum characterization result diagram of the FAPbCl3 perovskite nanocrystals prepared in the present invention.

[0015] Figure 5 This is a graph showing the band gap characterization results of the FAPbCl3 perovskite nanocrystals prepared in the present invention.

[0016] Figure 6 This is a graph showing the results of steady-state fluorescence luminescence spectrum characterization of the FAPbCl3 perovskite nanocrystals prepared in the present invention.

[0017] Figure 7 It is a Fourier transform infrared spectroscopy characterization result diagram of the FAPbCl3 perovskite nanocrystal prepared in the present invention.

[0018] Figure 8 This is a graph showing the steady-state fluorescence luminescence spectrum characterization results of the perovskite film prepared from the FAPbCl3 perovskite nanocrystals prepared in the present invention.

[0019] Fig. 9 It is a flow chart of preparing FAPbCl3 perovskite nanocrystals in the present invention. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with embodiments:

[0021] Example 1: Preparation of FAPbCl3 perovskite nanocrystals

[0022] (1-1) Cleaning before preparation

[0023] Prepare several sample bottles, a set of filtration devices and several magnetic particles, and use deionized water, isopropanol and anhydrous ethanol for ultrasonic cleaning, each for 10-15 minutes. After the ultrasonic cleaning, put the sample bottles, filtration devices and magnetic particles in a drying oven at 50-60°C for drying. After drying, seal the sample bottles, filtration devices and magnetic particles with sealing film, and store them in a drying oven at room temperature for use.

[0024] (1-2) Preparation of FAPbCl3 perovskite solution

[0025] Weigh hydrochloric acid (HCl) at room temperature, and weigh nitrogen, nitrogen-dimethylformamide, dimethyl sulfoxide, lead acetate (CH3COOPb) and formamidine acetate (CH3COOFA) in a glove box. The weight percentages are: 0.1-20% hydrochloric acid solution, 0.1-25% nitrogen, nitrogen-dimethylformamide, 0.1-30% dimethyl sulfoxide, 2-50% formamidine acetate and 1-45% lead acetate. Put a magnet into a sample bottle containing the solution and place it on a magnetic stirrer for stirring at a speed of 100-300rpm. After the speed stabilizes, add lead acetate and stir for 10-15 minutes. After the lead acetate is completely dissolved, use a medicine spoon to slowly add formamidine acetate to the solution. After the formamidine acetate is completely added to the solution, slowly increase the speed to 500-800rpm and continue stirring for 8-14 hours.

[0026] (1-3) Preparation of FAPbCl3 perovskite nanocrystals

[0027] Prepare a suction filtration device, and place a polytetrafluoroethylene filter membrane with a pore size of 0.1-0.4 μm, and wet the filter membrane with a small amount of ethyl acetate. Pour the perovskite solution in (1-2) into the suction filtration device, place the filtered solid into a sample bottle and add excess ethyl acetate to ensure that the solid is completely submerged, then stir magnetically for 10-20 minutes, repeat the suction filtration and filtration 5-7 times, and then place the solid in a sample bottle for storage. Place the sample bottle opening in a tubular furnace, and evacuate the tubular furnace, keep the pressure display at -0.1 MPa, then introduce nitrogen to purge the tubular furnace until the pressure display remains at 0 MPa, repeat the vacuumization and nitrogen purge 5-7 times, and finally keep the vacuum in the tubular furnace, and keep the pressure display at -0.1 MPa.

[0028] (1-4) Characterization of products

[0029] The characterization spectrum of the FAPbCl3 perovskite nanocrystal prepared by the present invention is shown in the attached Figure 1-7As shown. The XRD spectrum of the FAPbCl3 perovskite nanocrystals prepared by the present invention shows that the nanocrystals show strong signals on the (100), (200), (101) and (102) crystal planes, with large peak intensity and narrow half-peak width, indicating that the prepared FAPbCl3 perovskite nanocrystals have a good degree of crystallization and a relatively consistent crystal plane orientation, proving that cubic phase FAPbCl3 has been prepared. According to the SEM characterization diagram, it can be seen that the prepared nanocrystals have uniform grain size, smooth grain surface, and grain size conforms to normal distribution, with most grains being 5-10μm. According to the UV absorption visible light spectrum and band gap attachment Figure 4 , 5 , indicating that the prepared nanocrystals have strong light absorption ability in the range of 200-425nm, and the absorption ability of ultraviolet light is most prominent, and the absorption limit is consistent with the material band gap width. According to the electron transition calculation formula, the band gap of the FAPbCl3 perovskite nanocrystal prepared by the present invention is 2.99eV, which is consistent with the theoretical optical band gap. Figure 6 The steady-state fluorescence emission spectrum shows that the sample has a strong luminescence ability at 421nm, indicating that the sample has few defects, good luminescence performance, and less non-radiative recombination. Figure 7 It can be seen that the Fourier transform infrared spectroscopy (FTIR) shows that 3400cm -1 The stretching vibration of NH is at 3260cm -1 The stretching vibration peak of CH is at 1720 cm -1 The C=N stretching vibration of FA is at 1620cm -1 is the deformation vibration of NH, 1340cm -1 The peak at 1050 cm-1 is due to the CH deformation vibration, and the peak at 1050 cm-1 is due to the CN stretching vibration, indicating the presence of formamidinium ions in the sample.

[0030] Example 2: Preparation of FAPbCl3 perovskite film

[0031] (2-1) Cleaning before preparation: Select several clean fluorine-doped tin dioxide conductive glasses (FTO) and scrub them with deionized water and detergent. Scrub each piece for 5-10 minutes and repeat 2-3 times. Use deionized water, isopropanol and anhydrous ethanol for ultrasonic cleaning successively, each for 10-15 minutes. After the ultrasonic cleaning, place them in a drying oven for drying, and then place them in a UV box for 10-20 minutes for use.

[0032] (2-2) Preparation of FAPbCl3 perovskite solution: The nanocrystalline powder prepared in Example 1 was dissolved in a DMF:DMSO (4:1) solution in a glove box at a concentration of 1.2-1.5 M.

[0033] (2-3)NiO xPreparation of thin film: 30-40 μL 6-9 mg / ml NiO x The solution is spin-coated on the glass described in (2-1) at 3000-4000 rpm for 20-30 seconds, and then annealed at 100-150° C. for 10-15 minutes.

[0034] (2-4) Preparation of FAPbCl3 thin film

[0035] Take 40-70 μL of the perovskite solution in (2-2) and spin coat it on the glass at 3000-4000 rpm for 25-30 seconds. After the spin coating, anneal at 100-110°C for 15-20 minutes.

[0036] (2-5) Characterization of FAPbCl3 thin films

[0037] The characterization spectrum of FAPbCl3 film is shown in the attached Figure 8 As shown in the fluorescence spectrum, compared with the Figure 6 It can be seen that the peak intensity at 421 nm is greatly reduced, indicating that the perovskite layer and the hole transport layer have good carrier transport properties.

[0038] The above description is an embodiment of the present invention and does not limit the patent scope of the present invention. Any improvement or transformation using the contents of the present invention specification and its drawings, or direct or indirect application in other fields, still falls within the patent protection scope of the present invention.

Claims

1. A method for preparing perovskite FAPbCl3 nanocrystals based on a solution method, characterized in that: The following steps are involved: 1) Hydrochloric acid, nitrogen, nitrogen-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), formamidine acetate and vinegar The lead acid is mixed and stirred to react to obtain a mixed solution; 2) filtering and washing the mixture obtained in 1); 3) The washed product is placed in a tubular furnace for heating and drying, and after cooling to room temperature, perovskite FAPbCl3 nanocrystals are obtained.

2. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: In step 1), the hydrochloric acid, nitrogen, nitrogen-dimethylformamide, dimethyl sulfoxide, formamidine acetate and lead acetate are respectively in weight percentage: 0.1-20% of hydrochloric acid solution, 0.1-25% of nitrogen, nitrogen-dimethylformamide, 0.1-30% of dimethyl sulfoxide, 2-50% of formamidine acetate and 1-45% of lead acetate.

3. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: The method comprises mixing and stirring hydrochloric acid, nitrogen-dimethylformamide, dimethyl sulfoxide, formamidine acetate and lead acetate, wherein the concentration of hydrochloric acid is 35-38%, the concentration of nitrogen-dimethylformamide is 99.5-99.99%, and the concentration of dimethyl sulfoxide is 99-99.99%. When mixing, firstly, lead acetate is quickly added to the hydrochloric acid, and stirred for 10-15 minutes. After the lead acetate is completely dissolved, formamidine acetate is slowly added. During the whole process, the pH value of the mixture is kept below 0-7.

4. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 2, characterized in that: Lead acetate and formamidine acetate were weighed in an environment with a humidity lower than 0.01 ppm (in a glove box), and the other experimental operations of step 1) and step 2) were all carried out in air.

5. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: The sample bottles, sand core filtration devices and magnets used in step 1), step 2) and step 3) are ultrasonically cleaned for 15-20 minutes using deionized water, isopropanol and anhydrous ethanol in sequence.

6. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: The step 1) involves mixing hydrochloric acid, nitrogen, nitrogen-dimethylformamide, dimethyl sulfoxide, formamidine acetate and lead acetate. When adding lead acetate and formamidine acetate to hydrochloric acid, the solution is stirred with a magnetic bar at a speed of 100-300 rpm; after slowly pouring formamidine acetate, the stirring speed of the solution is slowly increased from 100-300 rpm to 500-800 rpm, and stirring is maintained for 8-14 hours.

7. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: The mixture filtered in step 2) is white in color and no mixture adheres to the inner wall of the bottle.

8. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: In step 2), the solution used for the filtration is ethyl acetate, and the mixture is filtered 5-7 times using ethyl acetate. After the first four filtrations, the mixture is immersed in ethyl acetate and stirred for 10-20 minutes.

9. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 1, characterized in that: In step 3), after the sample is placed in the tube furnace, the tube furnace is purged with nitrogen for 5-6 times, and finally the tube furnace is evacuated and the pressure reading is maintained at -0.1 MPa.

10. The method for preparing perovskite FAPbCl3 nanocrystals based on a solution method according to claim 11, characterized in that: The tube furnace is vacuum dried, the temperature of the tube furnace is set at 45-60° C., the heating rate is 3-8° C. / min, and the insulation time is 20-48 hours.